Air quality in urban areas: Comparing objective and subjective indicators in European countries. (February 2021) - Chiarini, Bruno; D'Agostino, Antonella; Marzano, Elisabetta; Regoli, Andrea
Highlights: We provide a subjective indicator of urban air quality in European countries. Using an objective and a subjective indicator, we cluster European countries. Norther European countries are in the "good air quality" cluster. Many Eastern Europe countries seem to suffer from the "satisfaction paradox". Greece and Germany show features of the "satisfaction dilemma". Abstract: Urban areas are major consumers of environmental resources and thus often place unsustainable demands on natural resources. As half of the world's population (55%) lives in urban areas, the environmental degradation produced by cities threatens the health and quality of life of a fair share of the world's population. For these reasons, progress towards sustainable urban development must be monitored and measured through suitable indicators. With reference to the assessment of air quality as a specific dimension of environmental quality in urban areas, existing studies have introduced various methodologies that mostly focus on objective measures (typically, exposure to outdoor air pollutants) while neglecting measures based on individual perceptions. Our goal is to contribute to filling this gap. To this end, we explore the relationship between objective and subjective measures of urban air quality in European countries. While the objective indicator is based on concentrations of PM2.5, our subjective indicator is reconstructed from individual perceptions collected through the European Union Statistics on Income and Living Conditions (EU-SILC) sample survey. Finally, through a cluster analysis, we classify the countries into homogeneous groups based on the values of these indicators. Our analysis reveals several differences in the country rankings according to the two indicators. For one group of countries, both approaches converge, thus leading to more definitive conclusions. For other countries, the mismatch between the two indicators suggests that either approach alone is not able to capture the full picture on air quality in urban environments.